The kinetic mechanism of human uridine phosphorylase 1: Towards the development of enzyme inhibitors for cancer chemotherapy - Renck, Daiana; Ducati, Rodrigo G.; Palma, Mario Sergio [UNESP]; Santos, Diogenes S.; Basso, Luiz A. (Elsevier B.V., 2010)
Uridine phosphorylase (UP) is a key enzyme in the pyrimidine salvage pathway, catalyzing the reversible phosphorolysis of uridine to uracil and ribose-l-phosphate (R1P). The human UP type 1 (hUP1) is a molecular target for the design of inhibitors intended to boost endogenous uridine levels to rescue normal tissues from the toxicity of fluoropyrimidine nucleoside chemotherapeutic agents, such as capecitabine and 5-fluorouracil. Here, we describe a method to obtain homogeneous recombinant hUP1, and present initial velocity, product inhibition, and equilibrium binding data. These results suggest that hUP1 catalyzes uridine phosphorolysis by a steady-state ordered bi bi kinetic mechanism, in which inorganic phosphate binds first followed by the binding of uridine, and uracil dissociates first, followed by RIP release. Fluorescence titration at equilibrium showed cooperative binding of either Pi or RIP binding to hUP1. Amino acid residues involved in either catalysis or substrate binding were proposed based on pH-rate profiles. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cancer chemotherapy; Initial velocity; Product inhibition; Fluorescence spectroscopy; pH-rate profiles; Uridine phosphorylase kinetic mechanism